2020
DOI: 10.1155/2020/8680436
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling and Projection of Multi-CMIP5 Precipitation Using Machine Learning Methods in the Upper Han River Basin

Abstract: Downscaling considerably alleviates the drawbacks of regional climate simulation by general circulation models (GCMs). However, little information is available regarding the downscaling using machine learning methods, specifically at hydrological basin scale. This study developed multiple machine learning (ML) downscaling models, based on a Bayesian model average (BMA), to downscale the precipitation simulation of 8 Coupled Model Intercomparison Project Phase 5 (CMIP5) models using model output statistics (MOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…p r e c i p i t a t i o n a m o u n t s a l o n g w i t h t h e corresponding standard deviations comparing the GCM predictions from CGCM3, CSIROMk3 and HadCM3 with the observation values derived from rain gauge measurements further reveals the inadequacies of the GCMs in accurately predicting the variability in the annual rainfall. This is in consonance with previous studies which have shown the capacity of GCMs in predicting rainfall at higher resolution scales and the importance of downscaling techniques to provide improved forecasts and modelling (Xu et. al., 2020;Narimisa and Narimisa, 2018).…”
Section: Fig 2 Rainfall Deviation From 1960-2007 Meansupporting
confidence: 92%
“…p r e c i p i t a t i o n a m o u n t s a l o n g w i t h t h e corresponding standard deviations comparing the GCM predictions from CGCM3, CSIROMk3 and HadCM3 with the observation values derived from rain gauge measurements further reveals the inadequacies of the GCMs in accurately predicting the variability in the annual rainfall. This is in consonance with previous studies which have shown the capacity of GCMs in predicting rainfall at higher resolution scales and the importance of downscaling techniques to provide improved forecasts and modelling (Xu et. al., 2020;Narimisa and Narimisa, 2018).…”
Section: Fig 2 Rainfall Deviation From 1960-2007 Meansupporting
confidence: 92%
“…At the same time, it has been further studied in the field of machine learning [15,16]. [17]. is is to find out the rules between data by analyzing the characteristics and association of data and to mine all kinds of information needed by human beings at a deeper level.…”
Section: Sar Image Classification Algorithm Based On Gaussian Processmentioning
confidence: 99%
“…A novel method (ClimAlign) was introduced in [42] for unsupervised, generative downscaling of temperature and precipitation based on normalizing flows for variational inference. Further works [4,[43][44][45][46][47][48][49][50] opted for downscaling based on ML and DL, and they helped assess both strengths and weaknesses of such methods. The results reported in these studies show that downscaling models based on ML allow better performance with respect to the other statistical approaches presented in [51][52][53].…”
Section: Related Workmentioning
confidence: 99%